Emerging Roles of Long Non-coding RNAs in Chronic Neuropathic Pain - Wu, Wei; Ji, Xiaojun; Zhao, Yang (Frontiers in Neuroscience, 2019)
Chronic neuropathic pain, a type of chronic and potentially disabling pain caused by a disease or injury of the somatosensory nervous system ,and spinal cord injury, or accompanied by various chronic conditions, such as viral infections (e.g., post-herpeticherpetic neuralgia), autoimmune diseases, cancers, and metabolic disorders (e.g., diabetes mellitus), is one of the most intense types of chronic pain, which incurs a major economic burden and is a serious public health issue, with an estimated prevalence of 7%~10% in adults over throughout the world. Presently, the available drug treatments (e.g., anticonvulsants acting at calcium channels, serotonin-noradrenaline reuptake inhibitors, tricyclic antidepressants, opioids, topical lidocaine, etc.) in for chronic neuropathic pain patients are still rare and have disappointing efficacy, which are makes it difficult to relieve the patient’s’ painful symptoms, and, at best, they only try to reduce the patient’s’ ability to tolerate pain. Long non-coding RNAs (lncRNAs), a type of transcriptstranscript ofwith morelonger than 200 nucleotides and with no protein-coding or limited capacity, were identified to be abnormally expressed in the spinal cord, dorsal root ganglion, hippocampus, and prefrontal cortex under chronic neuropathic pain conditions. Moreover, there is a a rapidly growing body of data havehas clearly pointed out that nearly 40% of lncRNAs are existed exist specifically in the nervous system. Hence, it was speculated that these dysregulated lncRNAs might be participatedparticipate in the occurrence, development and progression of chronic neuropathic pain. In other words, if we deeply delve into the potential roles of lncRNAs in the pathogenesis of chronic neuropathic pain, this may open up new strategies and directions for the development of novel targeted drugs to cure this refractory disorder. In this article, we primarily review the status of chronic neuropathic pain, and provide a general overview of lncRNAs, the detailed roles of lncRNAs in the nervous system and its related diseases, and the abnormal expressions of lncRNAs and their potential clinical applications in chronic neuropathic pain. We hope that through the above description, readers can gain a better understanding of the emerging roles of lncRNAs in chronic neuropathic pain.